Using Recombinant Human Collagen With Basic Fibroblast Growth Factor to Provide a Simulated Extracellular Matrix Microenvironment for the Revascularization and Attachment of Islets to the Transplantation Region - Qunyan Zhu; Qunyan Zhu; Qunyan Zhu; Cuitao Lu; Xuan Jiang; Qing Yao; Xue Jiang; Zhiwei Huang; Yina Jiang; Lei Peng; Hongxing Fu; Yingzheng Zhao; et al. (Frontiers Media S.A., 2020)
Islet transplantation is considered a potential therapeutic option to reverse diabetes. The pancreatic basement membrane contains a variety of extracellular matrix (ECM) proteins. The abundant ECM is essential for the survival of transplanted islets. However, the ECM proteins necessary for maintaining islet vascularization and innervation are impaired by enzymatic digestion in the isolation process before islet transplantation, leading to destruction of islet microvessels. These are the primary concern and major barrier for long-term islet survival and function. Thus, it is crucial to create an appropriate microenvironment for improving revascularization and islet function to achieve better transplantation outcome. Given the importance of the presence of ECM proteins for islets, we introduce recombinant human collagen (RHC) to construct a simulated ECM microenvironment. To accelerate revascularization and reduce islet injury, we add basic fibroblast growth factor (bFGF) to RHC, a growth factor that has been shown to promote angiogenesis. In order to verify the outcome, islets were treated with RHC combination containing bFGF and then implanted into kidney capsule in type 1 diabetic mouse models. After transplantation, 30-day-long monitoring displayed that 16 mg-60 ng RHC-bFGF group could serve as superior transplantation outcome. It reversed the hyperglycemia condition in host rapidly, and the OGTT (oral glucose tolerance test) showed a similar pattern with the control group. Histological assessment showed that 16 mg-60 ng RHC-bFGF group attenuated apoptosis, promoted cellular proliferation, triggered vascularization, and inhibited inflammation reaction. In summary, this work demonstrates that application of 16 mg-60 ng RHC-bFGF and islets composite enhance the islet survival, function, and long-term transplantation efficiency.